An integrated solution for optimal generation operation efficiency through dynamic economic dispatch. (2021) - Wang, Qing-Guo; Yu, Ming; Liu, Jidong
Abstract: We propose a total and intelligent solution for optimal demand management for energy efficiency under the new framework of true dynamic economic dispatch (DED) which integrates advanced metering, new modelling for demand, dynamic load dispatch and bidding strategy together. It involves the following essential modules. (i) Dynamic economic dispatch is a true dynamic optimization formulation. With real time measurements and both supply and demand modelling, the optimization will produce the optimal plant operation modes and settings which give the highest efficiency of the overall system and are fed back to the plants for execution. (ii) Dynamic sensing is real time sensing and data acquisition system to access the real operating status of the generation plant with measurement of relevant variables. The big data technology is adopted for construction of the overall hardware and software to store huge volume of plant and market data and perform fast off line modelling and design as well as on line real time control. (iii) Dynamic modelling is model building to forecast energy demands and generation over time. Under the DED, these modules are well integrated to work together and achieve an optimal demand management for maximum energy efficiency. Its solution, verification and field implementation are reported.